Impact of gum chewing on recovery of bowel activity after caesarean section - ., Manisha; Duhan, Nirmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Childbirth is a memorable part in every woman’s life. Each labour experience is unique and calls for a celebration. Objective of this study was to evaluate the effect of gum chewing on recovery of bowel motility after caesarean section. Methods: This prospective randomized controlled trial was conducted on 220 women who had undergone cesarean section and were further sub-divided into two groups of 110 women each Group I (Study group, n=110) in whom chewing gum was advised postoperatively and Group II (Control group, n=110) who were managed as per standard departmental postoperative feeding protocol. Results: Mean age in Group A women was 24.86±3.89 years and 25.28±3.34 years in Group B. There was no statistically significant difference between the study and control group regarding their age, parity, occupation, LSCS/previous abdominal surgery, type of cesarean section, indications of cesarean section, skin incision, intraperitoneal adhesions. The mean time of bowel sound appearance in Group A was 3.27±0.95 and it was 8.22±2.0 hours in Group B. The mean time of passage of flatus was found to be 9.77±3.21 hours in Group A and 7.15±3.07 hours in Group B. In Group A, the mean time of passage of stools was 18.79±4.23 hours and it was 39.12±6.56 hours in Group B. Mean duration of hospital stay was significantly lesser (3.23±0.60 days) in gum chewing group than in the non-gum chewing group (4.18±1.28 days). Seventy-six (69.09%) women of Group A needed only one chewing gum before appearance of bowel sound / flatus / feces. Only three women required three chewing gums. Out of 31 cases, who required two chewing gums, five were of previous 1 LSCS and 12 were previous 2 LSCS, thus suggesting delayed return of gut motility in women with > 1 previous LSCS. Conclusions: It was evident that gum chewing, a form of sham feeding is considered as an effective and inexpensive method which hastens the return of gut motility after caesarean section.